Microsatellites in cassava (Manihot esculenta Crantz) : discovery, inheritance and variability - Chavarriaga Aguirre, Paul; Maya, M.M.; Bonierbale, Merideth W.; Kresovich, Stephen; Fregene, Martin A.; Tohme, Joseph M.; Kochert, G (1998)
Fourteen microsatellites containing GA-repeats were isolated and characterized in cassava (Manihot esculenta Crantz, Euphorbiaceae). Microsatellite heterozygosity (h) was estimated in 48 accessions using (32P)-end-labeled primers and in more than 500 accessions using fluorescence-based genotyping. Heterozygosity values ranged from 0.00 to 0.88 and the number of alleles detected varied from 1 to 15. The reproducibility of allele sizing was also assessed using fluorescence-based genotyping. The average inter-gel size difference was 1.03 nucleotides. Chi-square tests (?2) were performed to analyse segregation distortion and the linkage between alleles segregating from either or both parents in an F1 mapping population. Most microsatellite loci segregated in the expected 1?:?1, 1?:?2?:?1 or 1?:?1?:?1?:?1 ratio. Linkage was detected between loci segregating from either parent, and segregation distortion from the male parent was detected for locus GA-131. Approximately 80% of the microsatellites detected one or two alleles per accession, suggesting a low degree of microsatellite locus duplication, an unexpected finding for a putative allopolyploid, highly heterozygous species. The high h values of most microsatellites, their amplification in other Manihot taxa and their suitability for high-throughput, fluorescence-based genotyping, make microsatellites the marker of choice for germplasm characterization and saturation of the cassava map.